2018
DOI: 10.1038/s41598-018-35798-2
|View full text |Cite
|
Sign up to set email alerts
|

The utility of urinary CD80 as a diagnostic marker in patients with renal diseases

Abstract: CD80, which regulates T cell activation, may provide a differential diagnostic marker between minimal change disease (MCD) and other renal diseases, including focal segmental glomerular sclerosis (FSGS). However, recent reports show contrasting results. Therefore, we evaluated the utility of urinary CD80 as a diagnostic biomarker. We collected 65 urine samples from 55 patients with MCD (n = 31), FSGS (n = 4), inherited nephrotic syndrome (n = 4), Alport syndrome (n = 5) and other glomerular diseases (n = 11), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…11,15,26À28 A recent report did not show differences in the urinary CD80/ creatinine ratio in MCD with respect to other nephrotic diseases. 29 Of note, this study included only 4 FSGS patients (with an outlier), and one-third of MCD samples appeared to have high uCD80 levels, suggesting that subgroups of patients can be stratified according to their uCD80 levels. 29 Glomerular CD80 expression and uCD80 have also been suggested as predictors of abatacept response.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…11,15,26À28 A recent report did not show differences in the urinary CD80/ creatinine ratio in MCD with respect to other nephrotic diseases. 29 Of note, this study included only 4 FSGS patients (with an outlier), and one-third of MCD samples appeared to have high uCD80 levels, suggesting that subgroups of patients can be stratified according to their uCD80 levels. 29 Glomerular CD80 expression and uCD80 have also been suggested as predictors of abatacept response.…”
mentioning
confidence: 88%
“…29 Of note, this study included only 4 FSGS patients (with an outlier), and one-third of MCD samples appeared to have high uCD80 levels, suggesting that subgroups of patients can be stratified according to their uCD80 levels. 29 Glomerular CD80 expression and uCD80 have also been suggested as predictors of abatacept response. 15,17,30 Garin et al found strong glomerular CD80 staining in an MCD patient and weak staining in 2 FSGS samples.…”
mentioning
confidence: 88%
“…3-CSI test. The 3-CSI test was conducted as previously described 9 . Each subject mouse was acclimated to the test box by free exploration for 5 min before the test.…”
Section: Methodsmentioning
confidence: 99%
“…1 b,c, 2 d, 3 c,d, and Supplementary Fig. 2 d) as previously described 9 . To compare three or more groups, Dunnett’s test was used (Figs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation